Does Digital Inclusion Guarantee Digital Safety? Gendered Cyber Vulnerabilities among Urban Women Farmer Groups - Lian Agustina Setiyaningsih; Irma Mufita Yulistiowati; Muhammad Hanif Fahmi; Firmando Sion Prayoga (Jogjakarta Communication Conference (JCC), 2026)
The expansion of the platform-based economy in the digital era has driven increased digital inclusion for women’s groups, including urban women farmer communities. However, increased digital access and participation are not always accompanied by strengthened digital security. This study aims to analyze how urban women farmer groups construct and negotiate digital security literacy within platform economy practices, and to identify the gap between digital inclusion and account security sovereignty. This study fills a theoretical gap in the digital inclusion and digital literacy literature, which tends to emphasize individual access and skills without considering the distribution of security control based on social and gender relations. The study used a qualitative case study approach with one women’s farmer group in Malang City, Indonesia, involving eight informants (six members and two marketplace administrators). Data were collected through in-depth interviews, focus group discussions, and observations of digital communication practices. The results indicate that although the group’s digital engagement is high, centralized marketplace account management and password-sharing practices within the domestic sphere create a sense of delegated control. Digital security is understood as a matter of interpersonal trust, rather than systematic procedures, thus giving rise to relational vulnerabilities. The conclusion is that digital inclusion does not automatically guarantee digital security; Security sovereignty depends on the distribution of control within domestic and collective structures, so security literacy needs to be understood as a relational social practice.